Role of Service Quality Towards Customer Retention of Tropical Hut in Cubao Quezon City: Basis for Improvement Plan: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Tropical Hut is a fast-food restaurant chain in the Philippines, founded in 1962 by the Quefamily. It quickly became popular for its affordable and delicious burgers, fried chicken, andother fast-food staples, expanding to other parts of Metro Manila and the Philippines. Despiteincreasing competition, Tropical Hut has maintained its popularity and relevance in thePhilippine fast-food industry by rebranding and updating its menu offerings. Service quality isan essential component of business success. Focusing on this area can lead to increasedrevenue, customer retention, positive word-of-mouth, and a competitive advantage. Speed ofservice, quality of food, cleanliness, and hygiene, staff behavior and attitude, atmosphere, andambiance are the factors that affect the service quality of Tropical Hut.Customers rated the service quality at Tropical Hut as "satisfactory" but with room forimprovement. The highest-rated factors were food quality, taste, and price affordability. Thelowest-rated factors were interior design, customer service, and waiting time. Observations ofthe service process showed that slow customer service and poor food preparation planningwere contributing factors to long wait times.To improve their service quality, they must invest in interior design upgrades, staff training oncustomer service, and improving food preparation planning to reduce wait times. Continuousimprovement and innovation plans are essential for businesses that want to stay competitiveand successful in today's market. By regularly evaluating and improving their processes,products, and services, businesses can stay ahead of the curve and meet the changing needsand preferences of their customers. The researchers suggest exploring the impact of digitaltechnology on service quality in the food industry.
Keywords: Marketing